Nutrition in patients with traumatic brain injury: Nutrition in patients with TBI - Stojanović Milena; Janković Radmilo; Ranđelović Milica; Vasilijić Milena; Nikolić Aleksandar; Radeka Jovan (Serbian Journal of Anesthesia and Intensive Therapy)
Traumatic brain injury (TBI) is a condition with a high morbidity and mortality rate. From a medical point of view, little can be done to prevent primary brain injuries. After the initial injury, a cascade of events at the cellular and molecular level, including cell swelling, changes in cell membrane permeability, influx of immune or inflammatory mediators, and release of excitatory neurotransmitters result in so-called "secondary" brain damage. Optimization in energy and protein provision has taken its place lately in the fundamental concept of treatment in critically ill patients with moderate and severe brain trauma, together with reducing intracranial pressure and prevention of hypotension and hypoxia. Administration of medical nutrition adjusted to the phase of trauma in the right time of medical treatment, as well as choosing the most adequate method of nutrition with appropriate formulas, can decrease neuro inflammation, immunodeficiency and metabolic crisis. A particularly difficult and challenging task in patients with TBI are maintenance of glucoregulation and electrolyte balance, protein replacement, and fluid therapy. Therefore, medical nutrition plays a significant role in the recovery of neurotraumatized patients.